With Motivation as a Mediation Variable and the Effect of Placement and Workload on the High Turnover Intention of Outsourcing Employees of PT. Warga Utama Prima Mandiri - Mahardhika, Tries; Rachmawati, Mariana (DINASTI RESEARCH, 2025)
PT. Warga Utama Prima Mandiri in the field of helpers, operators, supervisors, managers, analysts, where in service companies are very dependent on existing human resources. This study aims to identify with motivation as a mediating variable and the effect of placement and workload on the high turnover intention of outsourcing employees of PT. Warga Utama Prima Mandiri. The results of hypothesis testing indicate that there is a significant relationship between with motivation as a mediating variable and the effect of placement and workload on the high turnover intention of outsourcing employees of PT. Warga Utama Prima Mandiri. The accuracy of good job placement not only directly affects the employee's desire to stay or move from work. A high level of workload can reduce employee motivation which then increases the desire to look for more supportive work. Job placement has a direct effect on turnover intention. Excessive workload can reduce employee motivation and encourage them to look for jobs that provide more appropriate and supportive workloads. The accuracy of good job placement not only directly affects the employee's desire to stay or move from work. A high level of workload can reduce employee motivation which then increases the desire to look for more supportive work.